PENDEKATAN AMPLIFIKASI STRUKTURAL DAN NON STRUKTURAL BERBASIS EVALUASI KESESUAIAN LAHAN DALAM PENGENDALIAN BANJIR - Ligal - Sebastian (Universitas Siliwangi, 2023)
Changes in land use along with the increase in population both in urban and rural areas, this is accompanied by problems and environmental damage, namely; flooding, garbage, and damage to drainage construction. To prevent floods, it is necessary to develop a strategy to control flood-affected areas (including watersheds) through a strategy of structural and non-structural amplification approaches in controlling them. The method used is a qualitative description and comparative descriptive to see the flood problems that occur in several locations from a technical and social perspective in handling them. In addition, a spatial analysis of the watershed area was carried out, field observations of objects affected by flooding to determine physical and social conditions using the land suitability evaluation method. Through structural and non-structural amplification approaches, watershed conditions, banks and settlements can be evaluated and optimized from time to time according to the conditions. The results showed that the structural amplification approach (based on land suitability evaluation) can be used to determine the form of flood control based on the suitability of land in several classes, namely quite suitable, almost suitable, and not suitable. While non-structural amplification through sociology and empowerment approaches. The concept of land suitability evaluation is an appropriate approach for residential areas and watersheds, as well as the social conditions of the local community.Â Keywords: Flood Control, Watershed Area, Structural-Non-Structural Amplification, Land suitability evaluation